Infection prevention and control: knowledge, determinants and compliance among primary healthcare workers in enugu metropolis, south-east nigeria - Casmir N. Ochie; Elias C. Aniwada; Eloka K. Uchegbu; Thaddeus C. Asogwa; Chika N. Onwasoigwe (Elsevier, 2022)
Summary: Introduction: Healthcare workers have lost their lives in significant numbers in the discharge of their duties as a result of a breach in Infection Prevention and Control (IPC) procedures. The increasing incidence of emerging and re-emerging diseases complicates this burden. Adequate IPC includes administrative, environmental and personal protective control measures. This study assessed the knowledge, determinants and compliance to IPC among primary healthcare workers in Enugu Metropolis. Methodology: A cross-sectional study was done using a semi-structured interviewer-administered questionnaire. A multi-stage sampling technique was used to select 300 eligible Health Care Workers in Primary Health Care facilities. Analyses were done using IBM-SPSS version 23. Ethical approval was obtained from the Health Research Ethics Committee of UNTH Enugu. Results: The majority of the respondents were Community Health Extension Workers (CHEWs) or Community Health Officers (CHOs) and nurses 122 (40.7%), 197(65.7%) were female; with a mean age of 39.86 ± 9.62 years. Only 254(84.7%) of the respondents had previous IPC training and 82(27.3%) of them had good knowledge of IPC. Needle-stick injury was identified as a source of occupational exposure to infections amongst 185(61.7%). A majority, 244(81.3%) could not correctly identify all the moments of hand washing. Conclusion: The demonstrated poor level of knowledge and compliance to IPC demands more research to unravel this existing gap. However, these conditions can be improved by training the workers on IPC.